Osebno reševanje iz vode s tubo - Kapus, Jernej (Šport (Ljubljana), 2017)
Rescuing a drowning person, who is exhausted and especially if they are irrational, is much safer with a tube than without one. The rescuer fastens the tube to their shoulders with a strap and places it under their upper arms, which adds to buoyancy and facilitates the rescue. The article describes several possible ways of jumping into the water and swimming with a tube as well as the rescue procedure. In the phase of approaching a drowning person, the procedure is the same, whereas in the rescuing phase it depends on the condition of the injured person who may be exhausted or irrational.
Keywords: buoyancy; drowning; plovnost; ponesrečenec; rescuer; reševalec; sport; šport; utapljanje; voda; water